2008
DOI: 10.1002/gps.2041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and anxiety symptoms in elderly patients admitted in post‐acute intermediate care

Abstract: Clinical depression and anxiety are common in older patients admitted in intermediate care. Anxiety is often but not invariably secondary to depression and both should be screened for. Depression is an important modifiable factor affecting length of stay. The benefits of structured management programmes for anxiety and depression in patients admitted in intermediate care are worthy of evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 29 publications
1
29
1
2
Order By: Relevance
“…In addition, an overlap between anxiety and depressive symptoms in patients with COPD is common and may increase the prevalence of patients with anxiety disorder [30,31], although in our study COPD remained associated with an increased risk of anxiety disorder even after adjusting for depression.…”
Section: Accepted M Manuscriptcontrasting
confidence: 49%
“…In addition, an overlap between anxiety and depressive symptoms in patients with COPD is common and may increase the prevalence of patients with anxiety disorder [30,31], although in our study COPD remained associated with an increased risk of anxiety disorder even after adjusting for depression.…”
Section: Accepted M Manuscriptcontrasting
confidence: 49%
“…All of these data add fuel to the ongoing debate about whether anxiety and depression are one or two distinct categories of disorders,45,60,61 not to ignore their comorbidity, which is also frequently mentioned 38,62,63. In light of the results obtained, which offer valid estimates in terms of the risks of suffering from the mental disorders under study, we have observed a link between finding it hard to fall asleep and the risk of being anxious rather than depressive or asymptomatic.…”
Section: Resultsmentioning
confidence: 98%
“…Depression is also one of the withdrawal symptoms that predicts relapse to smoking [10]. Patients with anxiety and depression often suffer from low self-confidence or self-efficacy, which may lead to worsened disease related coping [11] and poor self-care behaviors. Moreover, co-existing addiction and psychiatric disorders significantly decrease the cessation success rates in COPD smokers and increase mortality among these patients [12].…”
Section: Introductionmentioning
confidence: 99%